Extent of adoption of scientific practices in prawn farming - Sasikumar P K (Department of Management Studies, College of Fisheries, 1990)
This study was undertaken to probe into the present situation of prawn farming in Kerala. The study aimed at assessing the communication media used for the dissemination of scientific prawn farming practices, the communication media utilized by prawn farmers at awareness and adoption stages, extent of adoption of scientific practices, correlates of adoption behaviour and the reasons for non-adoption or partial adoption of scientific practices.